(untitled) (Biological Sciences - PJSIR, 2005)
In order to examine the genetic mechanisms controlling seed cotton yield and its components, four lines of Gossypium hirsutum L., MNH-554, Delcerro, Coker-304 and Albacala-(71)1190 were crossed in all possible combina- tions. Combining ability analysis of the data revealed that general combining ability effects were highly significant at p = 0.01, in respect of the number of bolls, seed cotton yield and lint percentage. The general combining ability variances were greater than specific combining ability variances, which showed the predominance of additive gene effects. Among the four parents, MNH-554 appeared to be the best general combiner for all the characters studied. Due to the preponderance effects of additive genes, it seems that single plant selection in segregating generations would be effective for improving the seed cotton yield and its various components